Hemofilije - Andoljšek, Dušan (Obzornik zdravstvene nege, 1998)
Hemophilia is a group of hereditary diseases with different pathogenesis. Mutation of the gene located on chromosome X is their common feature. Consequently, protein synthesis, t.e. factor VIII and factor IX is disturbed. There may be a low protein level or an infunctional protein. Clinical featuresdepend only on the level of the functional protein and are the same infactor VIII and factor IX deficiency. laboratory investigation is necessary to differentiate both deficiencies. The structure of the factor IX and factor VIII gene has been recognised in the 70-ies and 80-ies. Since the prenatal diagnosis of hemophilia and carriers of the hemophilia can be recognised.
Keywords: dedne bolezni; diagnostika; hemofilija